Pengaruh Pemberian Kombinasi Pupuk Organik Cair Berbasis Limbah Organik dan Pupuk NPK Terhadap Pertumbuhan Tanaman Bayam Merah (Amaranthus tricolor L.) Varietas Mira - Sagala, Rifca Ledia; Rahmi, Hayatul; Purnomo, Sulistyo Sidik; Rahayu, Yayu Sri (UNIVERSITAS LABUHANBATU, 2024)
Red spinach production is currently still relatively low and unstable due to lack of nutrition on agricultural land conditions. This study aims to obtain the best combination of doses of Liquid Organic Fertilizer(LOF) based on organic waste and NPK fertilizer, so as to increase the growth of red spinach (Amaranthus tricolor L.) Mira variety. The research method was used an experimental method with the singlefactor Randomized Block Design (RBD) with 8 treatments, namely: A (NPK 250 kg/ha), B (LOF 200 ml/l), C (LOF 100 ml/l + NPK 200 kg/ha), D (LOF 200 ml/l + NPK 200 kg/ha), E (LOF 300 ml/l + NPK 200 kg/ha), F (LOF 100 ml/l + NPK 150 kg/ha), G (LOF 200 ml/l + NPK 150 kg/ha), H (LOF 300 ml/l + NPK 150 kg/ha). Each treatment was repeated 4 times, resulting in 32 experimental units. Data analysis using the F test (α= 0.05) if significant, further tested with the Duncan Multiple Range Test (DMRT) at the level of 0.05. The results showed that there was not significant effect on all growth parametersof red spinach plants, but treatment C with a combination dose of 100 ml/l organic waste liquid organic fertilizer and 200 kg/ha NPK fertilizer gave the highest results for plant height 28 dap (73.36 cm) and number of leaves 28 dap (26.70 strands). Keywords: LOF, NPK fertilizer, growth, result, red spinach